IC 7268 Tentative Bituminous-And Lignite-Mine Inspection Standards -Revised September 1943 ? Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1943)
These inspection standards have been prepared for use in the Federal inspection of bituminous and lignite mines. They are a revision of "Tentative Coal-Mine Inspection Standards," published as Bureau of Mines Information Circular 7204 in February 1942 and employed a guide for Federal inspections. Numerous changes have been made in the original standards owing in part to recognition of shortages of some types of safety equipment due to the war, in part because of need of additional standards to cover certain mine conditions' arid' practices, and in part to conditions not foreseen when the original standards were prepared. About one-fourth of these standards are marked with an asterisk (*) as being of particular importance in preventing accidents in many coal mines; however; failure to carry out the suggestions made in such of the other standards as are applicable may also' lead' to the loss of lives.